Patient experience of the diagnosis and management of patellofemoral pain: A qualitative exploration. (February 2022) - Barber, Philip; Lack, Simon David; Bartholomew, Clare; Curran, Amy Jessica; Lowe, Catherine Minns; Morrissey, Dylan; Neal, Bradley Stephen
Abstract: Background: Patellofemoral pain (PFP) is common and long-term treatment outcomes are unsatisfactory. Qualitative exploration of diagnosis and management from the perspective of people with PFP is lacking. Objectives: To inform care and improve intervention delivery by exploring the experience of people with PFP regarding diagnosis and management. Design: Qualitative study with semi-structured interviews. Method: Online recruiting yielded a convenience sample of participants with PFP for semi-structured interview. Interviews were recorded, transcribed verbatim, and analysed using thematic analysis until theoretical saturation by multiple investigators to determine themes and sub-themes. Results: 12 participants were interviewed, with three themes identified; the value of diagnosis, the need for tailored (individualised) care, and the role of education. Participants viewed receiving a diagnosis as essential to guide management, yet one was rarely provided, causing uncertainty about pain mechanisms; "it's nice to be told what it is that's wrong" . Interventions needed to be tailored to the individual as not all participants responded in the same way to treatment(s) or had the same needs; "everyone copes and reacts differently" . Finally, participants viewed education as essential to empower them to understand and manage the condition; "if I'd have been given more information, I think I'd know how to deal with it more" . Conclusions: The overarching narrative from three themes was a desire for clearly communicated personalised care that meets individual needs. People with PFP desire a diagnosis to explain their pain, tailored interventions, and appropriate education to optimise their experience and outcomes. Highlights: Patients see a diagnosis as essential, but one was rarely provided. Interventions should be tailored as not all patients will respond in the same way. Education empowers patients and helps them understand PFP. People with PFP desire personalised care that meets their individual needs. Abstract : The high prevalence and poor prognosis demonstrate a clear need to optimise PFP management. This study aimed to inform care and intervention delivery by exploring patient experiences of the diagnosis and treatment of PFP using semi-structured interviews.